International relations of the rising spanish american states: 200 years of Ayacucho - Maúrtua de Romaña, Oscar (2024)
The construction of Latin America, as a vast and heterogeneous region, was strongly influenced by the independence processes in the nineteenth century. It should be noted that independence was not only a local process, but also transformed the global scenario by introducing new political actors, who then faced challenges such as the search for recognition, internal stabilization, institutional organization and the definition of borders. Through a historical-legal analysis, and an exhaustive review of bibliographic sources, this paper seeks to reflect on the internal tensions faced by the nascent Latin American states after the independence struggles, as well as on the process by which they managed to establish diplomatic and commercial relations with their peers, consolidating their presence in the world and configuring a certain regional identity. The legacy of this period is reflected in the current regional cohesion, represented by organizations such as the OAS and CELAC, which continue to promote unity and cooperation in the region.